El Sīāvaš mítico en algunas fuentes del zoroastrismo - Mohammadi Shirmahaleh, Shekoufeh (El Colegio de México, 2024)
The legend of Sīāvaš is one of the longest passages in the Shahnameh by the Persian poet Abolqasem Ferdowsi. Like many other heroes and kings of the Shahnameh, the characters of this legend have their most immediate antecedents in mythical figures recorded in the texts of Zoroastrianism. It is surprising, however, that Sīāvaš is hardly mentioned in these sources, in contrast to the prominence of his father Kāvūs, his son Xusrow or even his murderer Afrāsīāb. This paper examines four of the texts of the Zoroastrian tradition, namely the Avestā, the Bundahišn, the Dēnkard and the Mēnōg ī Xrad, with the aim of highlighting the few references to Sīāvaš and seeking an explanation for his insignificant presence in these sources.